Impact of Intellectual Capital on Firm Performance in Indian IT Companies - P, SHANEEB; SUMATHY, Dr. M. (The journal of contemporary issues in business and government, 2021)
The relationship of intellectual capital and firm performance has shown mixed results that lead more attention among the research scholars in global. This study focus on the relationship between intellectual capital and financial performance of IT companies in India by using value-added intellectual capital coefficient (VAICTM) model. The researcher selected sample of 88 IT companies on the basis of market capitalization and compiled data from audited annual reports during the period of 2009-2018. Accordingly, the multiple regression results show that both VAIC and components of IC (except CEE) significantly predicted the financial performance of Indian IT companies. Besides, structural capital efficiency was found strong significant predator of ROA (0.299) and human capital efficiency in the case of sales growth (0.594). Thus, Indian IT companies advised to give more attention of investment in employees, management structure and policies to increase their financial performance.